2022
DOI: 10.1136/bmjopen-2021-059452
|View full text |Cite
|
Sign up to set email alerts
|

Oral diazoxide versus placebo for severe or recurrent neonatal hypoglycaemia: Neonatal Glucose Care Optimisation (NeoGluCO) study – a randomised controlled trial

Abstract: IntroductionInfants with severe or recurrent transitional hypoglycaemia continue to have high rates of adverse neurological outcomes and new treatment approaches are needed that target the underlying pathophysiology. Diazoxide is one such treatment that acts on the pancreatic β-cell in a dose-dependent manner to decrease insulin secretion.Methods and analysisPhase IIB, double-blind, two-arm, parallel, randomised trial of diazoxide versus placebo in neonates ≥35 weeks’ gestation for treatment of severe (blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The NeoGluCO Study (ACTRN12620000129987) was a double-blinded, 2-arm, parallel randomized clinical trial of diazoxide vs placebo (trial protocol in Supplement 1) 8…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The NeoGluCO Study (ACTRN12620000129987) was a double-blinded, 2-arm, parallel randomized clinical trial of diazoxide vs placebo (trial protocol in Supplement 1) 8…”
Section: Methodsmentioning
confidence: 99%
“…Blinding was maintained by using opaque bottles labeled with a 4-digit random number and by adding a small amount of cornstarch to the placebo (4 g per 50 mL), making it visibly identical to the diazoxide suspension . Tetrad testing among hospital staff showed that the interventions had sensory equivalence and could not be distinguished …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations

Neonatal hypoglycaemia

Harding,
Alsweiler,
Edwards
et al. 2024
bmjmed
Self Cite